Design and Implementation of a Joint Training Program for Chemical Industry Fellows - Olga S. Kukurina; Marina E. Trusova; Yulia S. Vorotnikova; Anna Dell'Angelo; Flavio Manenti (Chemical Engineering Transactions, 2021)
The present paper describes a collaborative experience in the development and realization of a new joint educational program. The great motivation for designing the joint training program is the urgent need for the industrial sector to promote vocational training and enhance the leadership and professional skills of the staff, as well as to build sustainable partnerships between universities and chemical industry fellows. Therefore, the initiation stage and further implementation of the joint program were supported and facilitated by a business unit manager of Corporate University PJSC SIBUR within the framework of joint cooperation. The employee training under discussion was developed with PJSC SIBUR Holding (the largest petrochemical company in Russia) acting as a stakeholder to meet organizational objectives and participant expectations. The content of the designing program is indented to strengthen cross-training between background knowledge and technical applicative skills, and is based on the interdisciplinary and cooperative collaboration of Tomsk Polytechnic University and Politecnico di Milano. The key feature of the program under consideration is the use of a project-based approach. In this regard, the curriculum is designed to be flexible and based around term projects where the topics of investigation are suggested and selected by the participants in correlation with their professional duties. Final team project presentation (the attendees perform the deliverables of their project’s solution) and a critical review from Sibur’s experts are considered as the general assessment tool for this program. It should be mentioned, the deliverables of the performed projects were estimated at a high level by SIBUR experts. During the program implementation period, the following inferences and recommendations can be made: to reconsider the entry test content and requirements (to make them more customized), to raise the requirements towards a command of English. It was also offered to indicate a two-level system of training aimed at selection of the best learners (based on the results of the final task and achievement test completion) who will pursue the second level the focus of which is to introduce a module on computer modeling of specific processes and digital training in Chemical Engineering.